Entrepreneurship Education-Based MSME Empowerment Model for Local Spice and Food Processors in Ternate City: A Development and Initial Testing - Iswadi M. Ahmad, Wahjoedi, Agus Suman, Sugeng Hadi Utomo (Journal of Educational Studies, 2025)
Empowerment of Micro, Small, and Medium Enterprises (MSMEs) is generally still oriented towards conventional training and is not based on analysis of business needs or utilization of local potential. This study aims to develop an empowerment model for MSMEs processing spices and local food based on entrepreneurship education that suits the needs of MSMEs in Ternate City. The research method used Design Based Research (DBR) combined with action research, which included needs analysis, initial prototype development, and limited trials on 12 MSMEs. Data were collected through observation, interviews, focus group discussions, learning outcome tests, performance assessments, and observation of participant activities, then analyzed descriptively qualitatively and quantitatively. The results showed that the developed model consisted of entrepreneurship education materials based on local potential, practice-based learning, and learning tools in the form of an empowerment book and a facilitator's guide. The trial results showed that most participants achieved good to excellent categories across all materials, with the highest achievements in nutmeg processing (92%) and product packaging selection (91%). The model also increased active participant participation during learning. These findings indicate that the empowerment model based on entrepreneurship education is feasible to implement to improve the competence and competitiveness of MSMEs based on spices and local food.